European real estate markets during the pandemic: Is COVID-19 also a case for house price concerns? - Michael Koetter; Felix Noth (Leibniz-Institut für Wirtschaftsforschung Halle (IWH), 2022)
We use a new database on European real estate purchase and rental prices - the IWH European Real Estate Index - to document the relationship between staggered COVID-19 dynamics and real estate prices in 14 EU countries between January 2020 and December 2021. For most countries, we find no statistically significant response of monthly purchase and rental prices due to an increase of regional COVID-19 cases. For the UK we find that more COVID-19 cases depressed both purchase and rental prices significantly, but the economic magnitude of effects was mild during this sample period. In contrast, rents in Italy increased in response to hiking COVID-19 cases, illustrating the importance to consider heterogeneous crisis patterns across the EU when designing policies. Overall, COVID-19 dynamics did not affect real estate values significantly during the pandemic, thereby mitigating potential financial stability concerns via a mortgage lending channel at the time.
Keywords: 330; Immobilienmarkt; Immobilienpreis; Coronavirus; EU-Staaten